Autoimmunity, Infections, and the Risk of Monoclonal Gammopathy of Undetermined Significance - Sigurbergsdóttir, Aðalbjörg Ýr; Love, Thorvardur Jon; Kristinsson, Sigurður Yngvi (Frontiers in Immunology, 2022)
Various epidemiological studies, including case reports and -series in addition to larger, population-based studies, have reported an increased prevalence of monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma in individuals with a prior history of immune-related conditions. This is believed to support the role of chronic antigen stimulation in the pathogenesis of these conditions. In this short review, we summarize some of the largest population-based studies researching autoimmune diseases, infections, and the subsequent risk of MGUS, and discuss our understanding on its etiology and pathogenesis. Furthermore, we highlight important methodological limitations of previous studies in the field, but almost all studies on MGUS have been based on clinical, possibly biased, cohorts. Finally, we discuss future directions in researching the associations of MGUS and other disorders, including immune-related conditions, where screening studies play an important role.